Raman Spectroscopic Analysis of Cu-Ag-In-S/CdSe Core/Shell Quantum Dots Grown on Mesoporous TiO2 Substrates - Rahayu, Siti Utari; Candra, Andy (Talenta Publisher, 2025)
This study investigates the structural and vibrational properties of Cu-Ag-In-S/CdSe core/shell quantum dots (QDs) grown on the mesoporous TiO2 (mp-TiO2) substrates using Raman spectroscopy and 3D Raman mapping. The Raman spectra revealed distinct vibrational modes of AgInS2 and CdSe, compared to Cu-Ag-In-S, with a notable shift observed in the A1 mode (282.2 cm-1 to 260.8 cm-1), E and B2 modes (316.7 cm-1 to 326.4 cm-1), and an additional Cu-S mode (289.3 cm-1 to 283.4 cm-1). These shifts indicate significant interactions between the QDs and the substrate, as well as the presence of Cu and CdSe phases. 3D mapping provided spatial distribution data, showing enhanced Cu-incorporation and morphological variations across the substrates, with darker regions signifying Cu-enriched areas. The alterations in the Raman spectrum suggest a strong interaction between Cu-Ag-In-S and CdSe. The findings contribute to a deeper understanding of Cu-Ag-In-S/CdSe QDs, highlighting their potential to optoelectronic application.